Visceral leishmaniasis in wild canids – literature review (Research, Society and Development, 2022)
Visceral Leishmaniasis is a zoonotic parasitosis, spread through the bite of the vector infected by the protozoan that belongs to the genus Leishmania infantum (syn. chagasi), which affects humans and several species of wild and domestic animals. The dog is an important reservoir in the urban environment, since this zoonosis occurs in wild canids, such as the fox (Cerdocyon thous), hoary fox (Lycalopex vetulus), maned wolf (Chysocyon brachyurus) and bush dog (Spheotos venaticus), in the countryside or in captivity. Clinical studies are usually restricted to humans and dogs, not showing the others infected. In general, individuals are asymptomatic, but may present, in some cases: progressive weight loss, onychogryphosis, ophthalmic alterations and skin lesions such as ulcers, hyperpigmentation, desquamation, nasal hyperkeratosis and alopecia. Therefore, in this literature review, the objective will be to demonstrate the relevance of Visceral Leishmaniasis in wild canids in Brazil, covering the most diverse aspects, in addition to the impacts on Public Health.